Bayesian clinical reasoning in the first opinion approach to a dog with suspected thoracolumbar pain. (25th June 2022) - Khan, S.; Freeman, P.
Abstract : Whilst multi‐planar imaging has allowed advances in diagnosis and treatment of canine spinal cord disorders, it is sometimes inaccessible to pet owners leading to a reliance on imaging modalities and ancillary tests that are more readily available. For this reason, this essay considers how Bayesian clinical reasoning may aid in deciding which tests, if any, are most useful for the diagnosis of spinal disease in clinical practice and choosing reasonable empiric therapies.